The Impact of Work Environment, Communication, and Rewards on Employee Performance at The Hajj Financial Management Agency - M. Sopian Hadianto; Ratri Wahyuningtyas (Publikasi Indonesia, 2025)
The management of hajj pilgrimage funds by the Government of Indonesia requires high professionalism and accountability. The declining trend in employee performance at the Hajj Financial Management Agency (BPKH) in 2022, marked by a reduction in